Climate Change and Global Inequality: A Social Study of Climate Migration - Nofirman Nofirman; Iriana Bakti; Luis Santos; Momena Sultana (Journal of Social Science Utilizing Technology, 2025)
Background. Climate change is no longer a distant environmental issue but a present and intensifying force driving social and economic displacement across the globe. Vulnerable populations, particularly in the Global South, face disproportionate impacts in the form of rising sea levels, extreme weather events, and resource scarcity, often leading to forced migration. These dynamics underscore the intersection between climate change and global inequality, raising urgent questions about justice, adaptation, and human mobility. Purpose. This study aims to explore the social dimensions of climate-induced migration, focusing on how environmental stressors exacerbate existing inequalities and shape patterns of displacement. The research also investigates the role of governance, infrastructure, and international aid in either mitigating or perpetuating migration-related vulnerabilities. Method. A qualitative-dominant mixed-methods approach was employed, including ethnographic fieldwork in two climate-affected regions, semi-structured interviews with 30 climate migrants, and analysis of secondary data from international climate and migration databases. Data were thematically analyzed to uncover recurring patterns and socio-political contexts surrounding climate mobility. Results. Findings reveal that climate migration is not solely an environmental issue but deeply intertwined with poverty, weak governance, and limited access to resources. Migrants often face legal ambiguity, social exclusion, and economic instability in host regions. The study highlights a growing need for inclusive climate adaptation policies that address both environmental and social dimensions. Conclusion. The study concludes that addressing climate migration requires integrated strategies that bridge environmental sustainability, social equity, and human rights protections to ensure just and humane responses to climate-induced displacement.